Yield, quality and cost of jute (Corchorus species) seed production as influenced by herbicide application time - Meftahul Karim, Md.; Lutfar Rahman, Md.; Ferdush, Jannatul; Zablul Tareq, Md.; Mukul Mia, Md.; Tipu Sultan, Md.; Mujib Himel, Raihan (International Journal of Advanced Geosciences, 2020)
Jute is the most important fibre crop for Bangladesh and second important for world. Bangladesh requires about 6000 tons of jute seed. Among this quantity Bangladesh produce whole amount of Corchorus capsularis L. (white jute) seed but only very little amount of Corchorus olitorius L. (tossa jute) seed. Production of tossa jute seed is not too profitable because of high production cost for that reason farmers of Bangladesh are not interested to produce seed of tossa jute. And production cost of jute seed is mainly associated with labor cost that is mainly for weeding. This study was conducted to assess the best herbicide application time to enhance seed productivity, quality and reduction the cost of production. In this experiment two Corchorus species were grown using three different herbicide application times and no herbicide application used as control. The results indicated that for tossa jute (BJRI tossa pat-8) maximum plant population, plant height, branch/plant, capsule/plant, seed/capsule, seed yield, germination capacity, field emergence capacity, seed vigour and CVG were found in Control plot. Maximum 1000 seed weight and MGT were recorded in herbicide applied at 13th days after cutting transplanting. Maximum capsule length found at 10th days of herbicide application. For white jute (CVL-1) highest plant population, plant height, branch/plant, seed/capsule, capsule length, germination capacity, field emergence capacity, seed vigour and CVG were recorded in control plot. Highest capsule/plant, 1000 seed weight and seed yield were found in herbicide applied at 13th days after cutting transplanting. Maximum MGT found in herbicide applied at 16th days after cutting transplanting. Result revealed that herbicide use reduce the production cost of jute seed compare to manual seed production technology.Â Â Â